Impact of worker emigration on HIV epidemics in labour export areas: a molecular epidemiology investigation in Guangyuan, China. Issue 1 (December 2018) - Su, Ling; Liang, Shu; Hou, Xueqin; Zhong, Ping; Wei, Dongbing; Fu, Yu; Ye, Li; Xiong, Li; Zeng, Yali; Hu, Ying; Yang, Hong; Wu, Bo; et al.
Abstract We aimed to investigate the molecular epidemic characteristics and viral transmission patterns of HIV-1 in a typical labor export area, Guangyuan city, China. Based on conducting phylogenetic trees and molecular transmission networks, a phylogenetic analysis was performed on HIV-1pol sequences obtained from 211 migrant-history workers, 83 non-migrant-history individuals, and 21 migrant-history unknown individuals between January, 2012 and February, 2017 in Guangyuan city. Phylogenetic analysis revealed that CRF07_BC (48.3%, n = 152) and CRF01_AE (33.3%, n = 105) were the dominant strains in Guangyuan city, and circulated by multiple lineages with various epidemic characteristics. Geographic network analysis showed that Guangyuan city-related sequences with 20.3% CRF07_BC and 28.3% CRF01_AE were linked to that of other provinces, compared to that with 1.7% CRF07_BC and 5.0% CRF01_AE in cities of Sichuan. Molecular transmission network analysis further illustrated that migrant-history workers linked more sequences from other provinces than non-migrant-history individuals in both CRF07_BC (29.3% versus 0.0%, P = 0.013) and CRF01_AE (40.5% versus 10.0%, P = 0.001) networks. Our results highlighted that migrant-history workers in recent year played a vital role in fueling HIV-1 epidemic in Guangyuan city. Molecular transmission network analysis could be a useful approach for disclosing the transmission mechanism of HIV, which should be used in prevention and intervention efforts.